PENGARUH KOMPETENSI, MOTIVASI DAN KOMUNIKASI TERHADAP PRESTASI KERJA KARYAWAN PADA KANTOR KOMISI INDEPENDEN PEMILIHAN ACEH - Rika Klarista (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2025)
This study aims to determine the influence of competence, motivation, and communication on employee performance at the Aceh Independent Election Commission Office. The population of this study was all 65 employees at the Aceh Independent Election Commission Office, and the sample in this study was 65 employees at the Aceh Independent Election Commission Office using a census model. The analysis used in this study was multiple linear regression analysis. The results of the study indicate that competence, motivation, and communication simultaneously influence employee performance at the Aceh Independent Election Commission Office. There is a partial influence of competence on employee performance at the Aceh Independent Election Commission Office. There is a partial influence of motivation on employee performance at the Aceh Independent Election Commission Office. There is a partial influence of communication on employee performance at the Aceh Independent Election Commission Office. The implications of this study indicate that competence, motivation, and communication have a greater role in improving employee performance, one way of which is by implementing organizational values ​​that serve as guidelines for employees to help the Aceh Independent Election Commission Office improve employee performance to achieve agency goals.